Trend analysis of historical and future precipitation projections over a diverse topographic region of Khyber Pakhtunkhwa using SDSM. Issue 11 (19th October 2022) - Rahman, Ghani; Rahman, Atta-ur; Munawar, Saira; Moazzam, Muhammad Farhan Ul; Dawood, Muhammad; Miandad, Muhammad; Panezai, Sanaullah
Abstract: This study focuses on the spatio-temporal analysis of rainfall variability, trend patterns, and projected changes using GCM CCSM4 for RCP4.5 and RCP8.5 in Khyber Pakhtunkhwa. The historical rainfall variability (1971–2018), trend, and magnitude were assessed using Mann–Kendall and Spearman's Rho. In addition, to downscale GCMs data of precipitation at the regional level of Khyber Pakhtunkhwa, the SDSM conditional sub-model was applied. The monthly Mann–Kendall and Spearman's Rho trend test results revealed that most of the meteorological stations located in the northeastern mountains recorded a decreasing trend while Parachinar observed an increasing trend in almost all months except December. The trend results for seasonal rainfall showed a decreasing trend in winter, spring, and summer in the north and northeastern parts of Khyber Pakhtunkhwa whereas an increasing trend was observed in all seasons at Parachinar. The RCP4.5 projections depicted an increase in precipitation especially in the monsoon-dominating regions in comparison to the western disturbances, while decreasing rainfall projection was observed in RCP8.5. The projections for the summer and winter seasons depicted an increasing trend until the mid-century but in the latter half, a decline is registered. Such seasonal changes may initially cause flooding followed by drought, which calls for effective water management strategies. HIGHLIGHTS: The manuscript focuses on the rainfall variability in Khyber Pakhtunkhwa. The trend and magnitude of the trend have been detected in this study based on Mann–Kendall and Sen's Slope. It projects the rainfall in the region using 4.5 and 8.5 RCPs. Graphical Abstract